The evolution of host specialization in an insect pathogen. (1st October 2022) - Visher, Elisa; Uricchio, Lawrence; Bartlett, Lewis; DeNamur, Nicole; Yarcan, Aren; Alhassani, Dina; Boots, Mike
Abstract: Niche breadth coevolution between biotic partners underpins theories of diversity and co‐existence and influences patterns of disease emergence and transmission in host‐parasite systems. Despite these broad implications, we still do not fully understand how the breadth of parasites' infectivity evolves, the nature of any associated costs, or the genetic basis of specialization. Here, we serially passage a granulosis virus on multiple inbred populations of its Plodia interpunctella host to explore the dynamics and outcomes of specialization. In particular, we collect time series of phenotypic and genetic data to explore the dynamics of host genotype specialization throughout the course of experimental evolution and examine two fitness components. We find that the Plodia interpunctella granulosis virus consistently evolves and increases in overall specialization, but that our two fitness components evolve independently such that lines can specialize in productivity or infectivity. Furthermore, we find that specialization in our experiment is a highly polygenic trait best explained by a combination of evolutionary mechanisms. These results are important for understanding the evolution of specialization in host‐parasite interactions and its broader implications for co‐existence, diversification, and infectious disease management.